Analisis Penggunaan Media Digital dalam Program Lapor Mas Wapres - Nugraha, Irwan Abdu; Midhol, Ahmad Baihaqi (LPPM STISIP IMAM BONJOL, 2025)
This study aims to analyze the effectiveness of digital media use in the Lapor Mas Wapres Program using indicators developed by Bruhn et al. in Bimaskara (2020), namely: media attractiveness, media clarity, completeness of media information, and ease of media access. This research method uses a descriptive qualitative approach with content analysis techniques on the official Lapor Mas Wapres website. The results show that the digital media in this program has good visual appeal and navigation, but still lacks visual innovation and interactivity. The clarity of information is considered sufficient, but is not yet equipped with digital literacy to counter misinformation. In terms of completeness of information, this program provides a number of important information such as rules and terms of service, but lacks a comprehensive explanation of procedures and complaint mechanisms. Ease of access is relatively good through gadgets and WhatsApp, but is not yet fully friendly for people with disabilities.